NAVIGATING UNCERTAINTY AND COMPLEXITY: UNDERSTANDING HEALTHCARE PROFESSIONALS IN ADDRESSING PATIENT SAFETY CHALLENGES - Mira, José Joaquin (Srpski medicinski časopis Lekarske komore, 2024)
Providing optimal quality care is a challenge for professionals and healthcare systems around the world. Patients often rely on healthcare providers to assist them with their health concerns and to provide the safest and best possible care. However, despite the best efforts of healthcare providers to deliver high-quality care, unexpected adverse events can affect a patient. These events can be difficult for both patients and healthcare providers to deal with, particularly when they result in severe harm to the patient. In addition to the physical and psychological toll that these adverse events can take on patients, healthcare providers can also be emotionally affected. Healthcare providers who are involved in adverse events are often referred to as second victims. These professionals are not only directly affected by the adverse events experienced by the patient but also by the response that these events can provoke in other healthcare team members, directives, and within the health institution. Adverse events often have a systemic cause, meaning they can result from a combination of organizational, cultural, and environmental factors. Although usually the professional in charge of patient care who is directly related to the harm is singled out as responsible, there is a chain of events and professionals involved in most events. As a result, other healthcare team members may also be involved in the event, either directly or indirectly. This can create a sense of shared responsibility among the team and a shared sense of loss or guilt when adverse events occur.Healthcare providers and organizations need to recognize the impact of adverse events on patients and providers. By providing support and resources to second victims, healthcare organizations can help mitigate the emotional toll of these events and support providers in continuing to provide high-quality care to their patients.This paper outlines key elements for a better understanding of the second victim phenomenon and just culture principles, in accordance with the ERNST Consortium insights.
Keywords: adverse events; healthcare providers; medical errors; patient safety; just culture